Rock and paleomagneitc measurements of PS67/197-1 - Wenshen Xiao; Thomas Frederichs; Rainer Gersonde; Oliver Esper; Xu Zhang (PANGAEA, 2025)
The core was taken in 2005 during Polarstern cruise ANT-XXII/4 in the central Scotia Sea. Magnetic susceptibility, further paleomagnetic information and other proxies were measured on this and other cores in order to establish a detailed sediment stratigraphy of the Scotia Sea for the past 300 ka. A description of the methods is given in Xiao et al. (2016).